2021
DOI: 10.1088/1757-899x/1094/1/012107
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid ANOVA and LASSO Methods for Feature Selection and Linear Support Vector, Multilayer Perceptron and Random Forest Classifiers Based on Spark Environment for Microarray Data Classification

Abstract: Microarray dataset frequently contains a countless number of insignificant and irrelevant genes that might lead to loss of valuable data. The classes with both high importance and high significance gene sets are commonly preferred for selecting the genes, which determines the sample classification into their particular classes. This property has obtained a lot of importance among the specialists and experts in microarray dataset classification. The trained classifier model is tested for cancer datasets and Hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Embedded feature selection utilized a learning algorithm in order to select features [11]. One representative embedded feature selection method is the LASSO [27]. Albaldawi et al [27] proposed hybrid model ANOVA-LASSO methods and classification algorithms for microarray data classification.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Embedded feature selection utilized a learning algorithm in order to select features [11]. One representative embedded feature selection method is the LASSO [27]. Albaldawi et al [27] proposed hybrid model ANOVA-LASSO methods and classification algorithms for microarray data classification.…”
Section: Literature Surveymentioning
confidence: 99%
“…One representative embedded feature selection method is the LASSO [27]. Albaldawi et al [27] proposed hybrid model ANOVA-LASSO methods and classification algorithms for microarray data classification. Three different classification algorithms like Linear Support Vector Classifier (LSVC), Random Forest (RF) and Multilayer Perceptron Classifier (MLP) were used.…”
Section: Literature Surveymentioning
confidence: 99%
“…Hence, the process of feature dimension reduction was necessary for this model, which reduced the computational costs, avoided the problem of overfitting, and improved the generalization ability of the model. The feature selection methods used in this study included the analysis of variance (ANOVA) and the 𝓁 2,1norm minimization, 34,35 which were also implemented independently for six binary subtasks. The two feature selection algorithms were executed in sequence: First, the ANOVA algorithm was performed to initially select the features based on the intragroup variance and the inter-group variance; then, the 𝓁 2,1 -norm minimization algorithm was used for further feature selection; finally, a feature set suitable for the corresponding subtask was obtained.…”
Section: Independent Feature Selectionmentioning
confidence: 99%
“…Study on feature selection Lasso or Relief on RF found an accuracy of 85.6% [9]. A recent finding of using hybrid anova and lasso methods for feature selection of microarray data and testing on spark environment denoted that RF perform best with 100% in two dataset and 96% in one dataset in a less time consumed [10]. Other applications of machine learning approach particularly on predictive models could be found in various field of studies including intervention and prevention of diabetic retinopathy [11], diagnosis of Alzheimer's disease [12], prediction of dengue outbreaks [13] and heart failure [14], prediction and classification on future PM10 concentrations [15], forecasting reservoir water level [16], forecasting daily sales data [17] and rainfall prediction in flood prone areas [18] and brain MRI image classification for Alzheimer's disease [19].…”
Section: Introductionmentioning
confidence: 99%

Classification of Breast Cancer Subtypes using Microarray RNA Expression Data

Muhammad Shazwan Suhiman,
Sayang Mohd Deni,
Ahmad Zia Ul-Saufie Mohamad Japeri
et al. 2024
ARASET